Concrete approaches to peace: infrastructure as peacebuilding. (1st March 2018) - Bachmann, Jan; Schouten, Peer
Abstract: Do roads literally lead to peace? While seemingly a strange question to ask, today's peacebuilders certainly seem to think so. After decades of focus on questions of governance, today, instead, infrastructure primes in state- and peacebuilding missions in many fragile and conflict-affected societies. Peacebuilding efforts in places ranging from Somalia to Afghanistan to the Congo are, to a considerable extent, interventions in the built environment. While infrastructure has always been around in post-conflict reconstruction, today, infrastructure is mobilized during ongoing conflict, invested with aspirations of improving security and stability. To be sure, infrastructure played a big role in the formation of strong western states. But can we take this experience to try and forge political orders of concrete and steel? At a first glance, a theory of change that reorders societies by deploying the hidden powers of the built environment seems compelling, and measurable and concrete infrastructure outputs, additionally, fit perfectly within today's more pragmatic approaches to peace. However, based on examples from across the contemporary global peacebuilding landscape, we show that infrastructure neither amounts to a uniform force, nor is it clear what its impact on peace exactly is. What is certain is that infrastructure is profoundly entwined with contemporary peacebuilding, and that we therefore need to develop novel theoretical angles to come to terms with the ubiquitous politics of infrastructure.